PWE-138 The outpatient burden of coeliac disease on a district general hospital: an 11 year retrospective review. (17th June 2017) - Bhuva, M; Patel, J; Sakthivel, GD; Rostami, K; Marsh, MN; Johnson, MW
Abstract : Introduction: Coeliac disease remains a huge burden on the NHS with an incidence of 1 in 100 people. For the last 10 years there has been a drive from our CCG to discharge patients with confirmed coeliac disease back to their GP's for community based management. In this study, we set about establishing the total cost and demand made on the Luton and Dunstable District General Hospital in managing these coeliac patients, despite this policy. Main objective: To assess the demand and the cost of outpatient services provided to patients with coeliac disease, and to understand what outpatient services were being utilised. Method: Luton and Dunstable Hospital has a database of 1317 patients with a diagnosis of coeliac disease. Using the hospital's coding system we were able to analyse the total number of outpatient appointments (OPAs) made over 11 years between 2005 and 2016. Total costs were calculated using a range of different prices for different specialties, and depending on whether the OPAs were new (£210-£265) or follow up (£83-£136) clinic appointments. In addition, the burden on certain specialties was analysed in more detail. Results: Over the 11 year period, 33 150 outpatient appointments were made by the 1317 coeliac patients (25.17 per person; 2.29 per person per year) costing the local trust a total of £5, 167, 396. The total number of appointments per patient ranged from 1 to 167. Including paediatrics, there were 3, 235 Gastroenterology appointments made (836 new and 2399 follow-up) costing a total of £4 62 858. There were also 1468 appointments made with the dietitians (473 new and 995 follow-up) costing a total of £2 22 024 and 949 OPAs made with the Dermatology team (356 new and 592 follow-up) costing a total of £1 49 848. Interestingly, there were also 1451 OPAs made with the Ophthalmology team and 906 appointments made with the Audiology team. Conclusion: Over 11 years, the 1317 patients made 33, 150 OPAs, 10.25% of which were with the Gastroenterology team. The total cost of OPAs with specialties other than Gastroenterology was £4, 704, 538, however a large proportion of this cost, including Dietetic and Dermatology appointments, were likely to be related to the coeliac burden. In addition, with the established link between coeliac disease and ophthalmological manifestations secondary to associated autoimmune disease and nutritional deficiency, the burden of Ophthalmology OPAs was high in this group. Finally, there was also an unexpectedly high number of Audiology OPAs raising the suspicion that extra-intestinal manifestations of coeliac disease may be contributory. There is little in the literature regarding the auditory sequelae of coeliac disease, so further work in this area is needed. Disclosure of Interest: None Declared